2020
DOI: 10.3389/fimmu.2020.00272
|View full text |Cite
|
Sign up to set email alerts
|

Demeclocycline Reduces the Growth of Human Brain Tumor-Initiating Cells: Direct Activity and Through Monocytes

Abstract: Myeloid cells that infiltrate into brain tumors are deactivated or exploited by the tumor cells. We previously demonstrated that compromised microglia, monocytes, and macrophages in malignant gliomas could be reactivated by amphotericin-B to contain the growth of brain tumorinitiating cells (BTICs). We identified meclocycline as another activator of microglia, so we sought to test whether its better-tolerated derivative, demeclocycline, also stimulates monocytes to restrict BTIC growth. Monocytes were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Furthermore, patients whose tumors had a higher ratio of microglia-specific transcripts (P2RY12) to tumor associated macrophage (TAM)-specific transcripts (CD163) displayed longer overall survival (Figure 4J), suggestive of microglial anti-tumor activities. This is in line with recent studies that analyzed distinctive microglia markers and suggested that microglia are protective against glioblastoma (Chicoine et al, 2007;Hwang et al, 2009;Sarkar et al, 2014;Sarkar et al, 2020;Woolf et al, 2021).…”
Section: Microglia Directly Interact With Cd4 + Tils Via Mhc-ii To Su...supporting
confidence: 92%
“…Furthermore, patients whose tumors had a higher ratio of microglia-specific transcripts (P2RY12) to tumor associated macrophage (TAM)-specific transcripts (CD163) displayed longer overall survival (Figure 4J), suggestive of microglial anti-tumor activities. This is in line with recent studies that analyzed distinctive microglia markers and suggested that microglia are protective against glioblastoma (Chicoine et al, 2007;Hwang et al, 2009;Sarkar et al, 2014;Sarkar et al, 2020;Woolf et al, 2021).…”
Section: Microglia Directly Interact With Cd4 + Tils Via Mhc-ii To Su...supporting
confidence: 92%
“…DMC is clinically used to treat susceptible bacterial infections and can be systemically administrated due to its low toxicity in human cells, even neurons [ 28 ]. In order to uncover if this was also the case for DDMC, we first evaluated its impact on cell viability by measuring MTT turnover [ 17 ] in SH-SY5Y cell cultures, using similar concentrations as those used by Braun et al for DMC [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is used as a broad-spectrum antibiotic, but may be more often used to treat chronic syndrome of inappropriate secretion of antidiuretic hormone (SIADH) ( Miell et al, 2015 ). According to reports, DMCT is expected to be used as a contrast agent for intraoperative detection of brain tumors ( Sarkar et al, 2020 ). In our study, we collected 6 MDR clinical isolate strains of P. aeruginosa for combination therapy.…”
Section: Discussionmentioning
confidence: 99%